In vitro gastrointestinal digestion simulation screening of novel ACEI peptides from broccoli: mechanism in high glucose-induced VSMCs dysfunction - Zhang, Shuzhi; Guo, Jingjing; Suo, Shikun; Ju, Li; Jiang, Zhaoqiang; Dong, Pingshuan; Wang, Yanli; Dang, Yali; Du, Laijing (Frontiers in Nutrition, 2025)
Many natural angiotensin-converting enzyme inhibitory (ACEI) peptides have been widely studied. However, their stability in vivo is poor in most cases. In this study, peptides were initially digested from broccoli in vitro, and absorption was simulated by Caco2 cells transport and then analyzed by Peptideomics and molecular docking. Subsequently, the mechanisms were verified using a high glucose-induced vascular smooth muscle cells (VSMCs) dysfunction model. Results showed that ACEI activity of broccoli crude peptide increased by 70.73 ± 1.42% after digestion. The enzymatic hydrolysates of crude broccoli peptides before and after digestion were detected by HPLC. The digested crude peptides were highly stable (with a stability level > 90%) in the intestine and possessed a strong absorptive potential. Five peptides with high stability and strong permeability were first identified, including HLEVR, LTEVR, LEHGF, HLVNK, and LLDGR, which exhibited high activity with IC50 values of 3.19 ± 0.23 mM, 17.07 ± 1.37 mM, 0.64 ± 0.02 mM, 0.06 ± 0.01 mM, and 2.81 ± 0.12 mM, respectively. When the VSMCs model was exposed to Ang II, the expressions of PCNA, MMP2, and Bcl2 were increased, while the expression of BAX was inhibited. When the VSMCs was exposed to high glucose (HG), the Ang II concentration significantly increased. This indicates that HG elevated Ang II levels. Finally, five peptides significantly attenuated Ang II-induced VSMCs proliferation and migration by down-regulating AT1R expression and inhibiting ERK and p38 MAPK phosphorylation. Notably, in exploring VSMCs dysfunction on a high glucose-induced model, ACEI peptides resulted in down-regulation of ACE and up-regulation of ACE2 expression. Therefore, it can be further referenced for the functional food against hypertension and cardiovascular diseases.